Greening of the essential activities of an Engineering School: a case study in the Area/Department of Production Engineering - Izidoro, Gabriela Dupas; Jabbour, Charbel José Chiappetta [UNESP] (My University, 2012)
This article analyzes the inclusion of the issue of “environmental management” in the department of Production Engineering of the “Alfa” School of Engineering. For this, a case study was conducted at the School of "Alpha" Engineering, with a focus on the area of Production Engineering. Professors were interviewed; documents were reviewed as well as information collected from direct observations by of one of the authors of this article. It was observed that the department of Production Engineering at the Alpha School of Engineering has been developing activities covering all those aspects proposed by Jabbour [8]. "Environmental management" has been included in the curriculums of: (a) Teaching: in the creation of undergraduate courses (obligatory) and graduate Master's degree (optional), (b) Research: formalization of research groups in environmental management for the creation of master’s post graduation research, formalization of environmental management as one of the subjects that should be chosen by candidates for a Professorship in the area of production engineering; (c) Extension: Course in Environmental Management, Symposium (which in recent years has been focusing on environmental issues), creation of sustainability indicators for universities, (d) University Management: initiatives to raise awareness, distribution of reusable mugs and installation of special bins for selective collection in the Campus.
Keywords: Environmental management; School of engineering; Production engineering; Case study